Woorden van een gezond verstand : De invloed van de Verlichting op de in het Nederlands uitgegeven preken van 1750 tot 1800. Monografie en bibliografie - Bosma, Jelle Johannes, (Bibliotheca Bibliographica Neerlandica ;, 1997)
The role of religion in Dutch Enlightenment is reconstructed here by analysing the 1.753 printed sermons in Dutch published between 1750 and 1800. These are extensively described in the second part of this study (pp. 445-701). The bibliography covers all major collections in the Netherlands and abroad, allowing for further research. Fully indexed and with a comprehensive summary in English.